2010
DOI: 10.1182/asheducation-2010.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Elderly Patients: An Emerging Problem for the 21st Century

Abstract: Anemia is a significant problem in elderly patients. Although many anemic elderly patients can be diagnosed with nutritional deficiency, anemia of chronic inflammation or comorbid diseases that explain their decreased hematocrit, the etiology of anemia in a significant fraction remains obscure. There is evidence to suggest that the hematopoietic stem cell displays increasing erythropoietin (EPO) resistance with age. EPO levels rise in elderly, nonanemic patients, and it is hypothesized that there is an interpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 37 publications
2
57
0
8
Order By: Relevance
“…The induction of hepcidin by the pro-inflammatory cytokines IL-6, IL-1 and TNF is thought to result in the retention of iron inside the host cells, limiting its availability for pathogens. Pro-inflammatory cytokines are also correlated with AI in non-infectious conditions, such as that observed in the elderly (Vanasse & Berliner 2010). Our data showed increased IL-1β levels in the serum of LP and IL-1β levels were positively correlated with urinary hepcidin levels.…”
Section: Discussionsupporting
confidence: 66%
“…The induction of hepcidin by the pro-inflammatory cytokines IL-6, IL-1 and TNF is thought to result in the retention of iron inside the host cells, limiting its availability for pathogens. Pro-inflammatory cytokines are also correlated with AI in non-infectious conditions, such as that observed in the elderly (Vanasse & Berliner 2010). Our data showed increased IL-1β levels in the serum of LP and IL-1β levels were positively correlated with urinary hepcidin levels.…”
Section: Discussionsupporting
confidence: 66%
“…Some studies demonstrated erythropoietin resistance as a pathophysiological phenomenon in HIVinfected patients (9), in which circulating auto-antibodies against endogenous erythropoietin blunted the normal physiological cytokine response to anemia. Vanasse et al (29) reported that erythropoietin resistance was found in the hematopoietic stem cells of aging individuals, and that senescence was related to enhanced expression of inflammatory cytokines that positively regulated erythropoietin resistance, leading to anemia in older age. Older age was found to be an independent risk factor for anemia in this study.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The observed association of severe anemia with advanced age, diabetes, and renal insuf- ficiency has been reported in previous registries of patients undergoing PCI [3][4][5] and reflects well-known clinical relationships. [21][22][23] Accordingly, the relatively high prevalence of anemia in patients with CAD undergoing PCI as compared with patients in a primary care setting 24 may be explained by common risk factors such as advanced age, diabetes, and chronic kidney disease. In addition, anemia may precipitate myocardial ischemia and unmask significant coronary steno- Full model for definite ST and definite or probable ST adjusted for type of stent generation and propensity score.…”
Section: Discussionmentioning
confidence: 99%